KEPEMIMPINAN PEREMPUAN DALAM ISLAM - Haris, Munawir (Universitas Islam Negeri Raden Intan Lampung, 2015)
THE LEADERSHIP OF WOMEN IN ISLAM: The role of women in a religious society to the question of who and what women are, the answer to which is found in the Koran. In these sacred Islamic verses the role and nature of women have been described by Allah, the almighty creator of us all. Despite the traditional multi-ethnicity of Ismaic tradition society’s social fabric, however, Islam as a universal religion for the entire country has shaped the structure of Islam’s society and the mentality of its citizens. Within the Islamic religious belief and the Koran, the belief is that women were created for the main purpose of their husbands. In fact, the Islam is universal religion. This articale analisise about existence woman in the leadership in Islam as universal religion.